Sustained censorship in DZ (2026-06) (Algeria) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Algeria. Data sourced from OONI.
Censorship Incident ID: DZ-2026-0112. Severity: critical. Confidence: 72%